JEJAK ISLAM DI TANAH KESULTANAN BUTON - Rijaal, Muhammad Khaerun (Fakultas Dakwah dan Komunikasi UIN Sunan Kalijaga, 2020)
The traces of Islam in the region of Buton Sultanate are rarely described by historians and preacher. This paper aims to explore the history of Islam in Buton. This article is result of a qualitative research with historical approach. The study found that the traces of Islam in the land of the Buton Sultanate can be known about the entry of Islamic teachings in the Buton which is able to change its system of government from a kingdom to a sultanate and also the traces of Islam left behind can continue through educational institutions. This was influenced by one of the figures who was very influential in the process of Islamization in the Buton Sultanate. Jejak islam yang berada di tanah kesultanan buton jarang untuk diketahui oleh sebagian ahli sejarawan yang berkecimpung didunia sejarah dan juga dakwah. Hal ini yang membuat penulis untuk memaparkan history mengenai jejak islam yang ada di tanah buton. Artikel ini merupakan penelitian jenis kualitatif dengan menggunakan pendekatan studi history sehingga jejak islam ditanah kesultanan buton bisa diketahui tentang masuknya ajaran islam yang ada ditanah buton yang mampu merubah sistem pemerintahannya dari kerajaan menjadi sebuah kesultanan dan juga jejak islam yang ditinggalkan dapat terus berlanjut melalui lembaga pendidikan. Hal ini dipengaruhi oleh salah satu tokoh yang sangat berpengaruh dalam proses islamisasi di tanah kesultanan buton